Human–robot collaboration in industrial applications: Safety, interaction and trust. (6th July 2017) - Maurtua, Iñaki; Ibarguren, Aitor; Kildal, Johan; Susperregi, Loreto; Sierra, Basilio
Human–robot collaboration is a key factor for the development of factories of the future, a space in which humans and robots can work and carry out tasks together. Safety is one of the most critical aspects in this collaborative human–robot paradigm. This article describes the experiments done and results achieved by the authors in the context of the FourByThree project, aiming to measure the trust of workers on fenceless human–robot collaboration in industrial robotic applications as well as to gauge the acceptance of different interaction mechanisms between robots and human beings.